Peran Kelompok Wanita Tani Bangun dalam Meningkatkan Kesadaran Gizi Melalui Program Gerakan Menanam Pangan di Pekarangan (GEMPAR) dan Pasar Tani - Maghfiroh, Wulan; Euriga, Epsi; Hermawan, R (Jurnal Agroteknologi (Agronu), 2025)
Awareness in nutritional fulfillment has a role in achieving optimal daily nutritional fulfillment. This lack of awareness related to nutrition will cause nutritional problems, one of which is stunting. Lendah is one of the areas that has a high number of stunting compared to other sub-districts in Kulon Progo (DataKu, 2022). The stunting rate in Lendah reached 211 toddlers. Alternatively, one way to overcome stunting is to work together through organizations in the community. Women have an important role in increasing nutritional awareness. Through the Women Farmers Group (KWT), women can be actively involved in utilizing the potential of natural resources to increase nutritional awareness. The purpose of this study is to determine the relationship between the role of KWT and the level of nutrition awareness through the Movement to Plant Food in the Yard (GEMPAR) and the Farmers Market program at KWT Bangun. This research was carried out in Ledok Hamlet, Sidorejo Village, Lendah District, Kulon Progo Regency. Data collection was carried out through interviews with 30 KWT members. Data analysis used descriptive analysis and Spearman Rank correlation analysis. The results of the study show that the role of KWT as a learning class is in the category of playing a very role, while as a vehicle for cooperation and production units is included in the category of playing a role. For the level of nutritional awareness, it is in the high category. The relationship between KWT's role as a learning class and a vehicle for cooperation with the level of nutrition awareness through the GEMPAR and Farmers Market programs is in the medium category. Meanwhile, the role of KWT as a production unit for nutrition awareness is included in the weak category. Therefore, it is necessary to increase the role of production units in order to increase the relationship to increase nutritional awareness